The Influence of Adversity Quotient on Anxiety in Final Year Students of the Department of Architecture Engineering Sam Ratulagi University Manado - Rachman Febrianto; Meike E. Hartati (International Consortium of Education and Culture Research Studies, 2020)
This study aims to determine the effect of adversity quotient on the anxiety of final year students who are preparing their final project. This study uses quantitative methods and this type of research is a simple linear regression research that aims to determine the effect of independent variables on the dependent variable, while the one that will be examined is the effect of adversity quotient on anxiety in students in the preparation of the final project at the Department of Architecture, Sam Ratulangi University, Manado. Characteristics of the sample are students of the Department of Architecture, Sam Ratulangi University, Manado, who have contracted a final assignment course, which consists of class of 2010, 2011, 2012 and 2013. The sampling technique used in this study is saturated sampling. The magnitude of the effect of adversity quotient on student anxiety can be seen from the r value of 0.979 with the coefficient of determination r2 = 0.958. This means that there is an effect of adversity quotient on student anxiety with the influence of the independent variable (X) of 95.8% on student anxiety and the remaining 4.2% is influenced by other factors. Based on this fact, it can be said that the adversity quotient does have a role or influence on reducing anxiety in students who are doing the final project.